Respuesta :

Answer:

1 , 3 , 4

Step-by-step explanation:

1)

[tex] {8}^{7} \: . \: {8}^{ - 12} \\ = {8}^{7 + ( - 12)} \\ = {8}^{ - 5} \\ = \frac{1}{ {8}^{5} } \\

2)

[tex] \frac{ {7}^{4} }{ {7}^{ - 3} } \\ = {7}^{4 - ( - 3)} \\ = {7}^{4 + 3} \\ = {7}^{7} \\

3)

[tex] { (\frac{1}{3} )}^{2} . \: {( \frac{1}{3} )}^{9} \\ { (\frac{1}{3}) }^{2 + 9} \\ { (\frac{1}{3} )}^{11} \\ [/tex]

4)

[tex] \frac{ {( - 5)}^{6} }{ {( - 5)}^{10} } \\ = {( - 5)}^{6 - 10} \\ = {( - 5)}^{ - 4} \\ = \frac{1}{ {( - 5)}^{4} } \\ [/tex]